2004
DOI: 10.1088/0022-3727/37/6/021
|View full text |Cite
|
Sign up to set email alerts
|

The response of polyether ether ketone to one-dimensional shock loading

Abstract: The behaviour of the polymer polyether ether ketone (PEEK) has been investigated under conditions of one-dimensional shock loading. This has involved measurement of the Hugoniot in terms of stress, shock velocity and particle velocity, and measurements of the lateral stress, which have been used to determine the shear strength, and its variation with shock stress. Analysis of the relationship between shock velocity and particle velocity shows a simple linear response, in common with many other materials. Shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 26 publications
7
26
1
Order By: Relevance
“…Such behaviour has been seen in a number of other materials, including metals such as titanium aluminides [26] and polymers such as polyether ether ketone [27], epoxy [28] and polycarbonate [29]. Further, independent measurements of the shear strength in these materials [26,27,29,30] confirmed that the shear strength did indeed increase with shock stress. Therefore, it would appear that in the through thickness orientation, the response to shock loading is controlled in large part by the epoxy binder phase.…”
Section: Discussion 14mentioning
confidence: 56%
“…Such behaviour has been seen in a number of other materials, including metals such as titanium aluminides [26] and polymers such as polyether ether ketone [27], epoxy [28] and polycarbonate [29]. Further, independent measurements of the shear strength in these materials [26,27,29,30] confirmed that the shear strength did indeed increase with shock stress. Therefore, it would appear that in the through thickness orientation, the response to shock loading is controlled in large part by the epoxy binder phase.…”
Section: Discussion 14mentioning
confidence: 56%
“…In metals, c 0 has been equated with the measured bulk sound speed (c B ), thus this discrepancy needs explanation. However, this behaviour has been observed in a number of other polymers, both by ourselves (see for example PEEK [17] and epoxy resins [16]) and in the compendium of polymer shock data published by Carter and Marsh [32]. In semicrystalline polmers [24], it was suggested that this be due to a deviation below the accepted linear response at very low particle velocities by a transition from elastic to inelastic behaviour in the stronger crystalline phase.…”
Section: Methodsmentioning
confidence: 67%
“…In all four materials, a significant increase in shear strength was also observed behind the shock front [17,18], again ascribed to a degree of tacticity between adjacent polymer chains. However, in the case of fluorinated polymers such as polytetrafluoroethylene (PTFE), PCTFE and polyvinylidene difluoride (PVDF), the situation is rather different [23,24].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations